Ready set remember : short-term auditory memory activities - Mense, Beatrice Ruby (Acer Press, 2006)
Ready Set Remember is a rich resource of information and activities for teachers with students whomay have auditory processing diffi culties. In order to listen well, a child must have adequate hearing, intactauditory processing skills and an 'active listening' mindset. This book helps teachers identify children with auditory diffi culties in the age range 5-8, before referringthem to an appropriate health professional. When the child returns to the classroom, Ready Set Rememberthen provides strategies and activities to encourage children's confi dence and improve their ability to effi cientlya.